Pengaruh pencucian sperma dan aras kuning telur terhadap kualitas sperma beku kambing peranakan ettawa=Influence of semen washing and egg yolk levels on quality of frozen buck semen of ettawa crossbred goat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
This research was conducted to investigate the effect of egg yolk level (15% and 20%) to dilute the washed and unwashed of semen on quality of frozen buck semen of Ettawa Crossbred goat. Semen were collected from two bucks using artificial vagina method. Data were analysed using analysis of variance in Completely Randomized Design for 23 factorial and continued with Duncan's New Multiple Range Test for semen quality. The results showed that the quality of semen (motility, pH, life and dead eel and abnormality) were highly significant different on washing and freezing process of semen, while levels of egg yolk were not significant different. The interaction between washing and freezing process were significantly different on motility and highly significant different on pH. Furthermore the interaction between washing, levels of egg yolk and freezing process were not significantly different. The research could be concluded that semen washed and 15% level of egg yolk for diluter could increase the quality of semen.